Bio-inspired fractal textile device for rapid sweat collection and monitoring. Issue 13 (8th June 2021) - Chen, Yen-Chi; Shan, Siang-Sin; Liao, Yu-Te; Liao, Ying-Chih
Abstract : A fractal collector with rapid sampling and high absorption flux is developed and combined with sensors for sweat real-time monitoring. Abstract : In this study, a new design concept in sweat collection was developed to achieve rapid and intact sweat sampling for analytical purposes. Textiles with fast water wicking properties were first selected and laser engraved into tree-like bifurcating channels for sweat collection. The fractal framework of the bifurcating textile channels was theoretically derived to minimize the flow resistance for fast sweat absorption. The optimized collector with designed fractal geometry exhibited thorough coverage of emerging droplets without overflow. Great collection efficiency was achieved with a short induction time (<1 minute after perspiration begins) and a maximum sweat collection flux up to 4.0 μL cm −2 min −1 without leakage. After being combined with printed sensors and microchips, the assembled sweat collection/sensing device can simultaneously provide measurements of salt concentration and sweat rate for wireless hydration state monitoring. The collection/sensing system also exhibited fast response times to abrupt changes in sweat rates or concentrations and thus can be used to detect instant physical conditions in exercise. Finally, field tests were performed to demonstrate the reliability and practicality of the device in real-time sweat monitoring under vigorous activities.